High temperature creep properties of ceramics United Kingdom Atomic Energy Authority Agreement No. SPO/A30081/EMR - Messer, P. F. (College of Aeronautics, 1967)
An existing high temperature rig, originally constructed for torsional creep on graphite was adapted for work on the high temperature creep properties of ceramics. Use of the rig, with minor modifications, for torsional creep on ceramics was not successful and major modifications to enable creep in tension and compression were carried out.